Atomistic insights into the selective therapeutic activity of 6-(2, 4-difluorophenoxy)-5-((ethylmethyl)pyridine-3-yl)-8-methylpyrrolo[1, 2-a]pyrazin-1(2H)-one towards bromodomain-containing proteins. (December 2021) - Akawa, Oluwole B.; Soremekun, Opeyemi S.; Olotu, Fisayo A.; Soliman, Mahmoud E.S.
Abstract: Cross-target effect has been one of the major mechanisms of drug toxicity, this has necessitated the design of inhibitors that are specifically tailored to target particular biomolecules. 6-(2, 4-difluorophenoxy)-5-((ethylmethyl)pyridine-3-yl)-8-methylpyrrolo[1, 2- a ] pyrazin-1(2H)-one (Cpd38 ) is an inhibitor possessing high inhibition rate and tailored specificity towards bromodomain-containing protein 4 (BRD4). In this research, we used an array of computational techniques to provide insight at the atomistic level the specific targeting of BRD4 by Cpd38 relative to the binding of Cpd38 with E1A binding protein P300 ( EP300); another bromodomain-containing protein (BCP). Comparatively, binding of Cpd38 improved the conformational stability and compactness of BRD4 protein when compared to the Cpd38 bound EP300. Also, Cpd38 induced a conformational change in the active site of BRD4 that facilitated a complementary pose between Cpd38 and BRD4 suitable for effective atomistic interactions. Expectedly, thermodynamic calculations revealed that the Cpd38 -BRD4 system had higher binding energy (−36.11 Kcal/mol) than the Cpd38 -EP300 system with a free binding energy of −15.86 Kcal/mol. Noteworthy is the opposing role Trp81 (acting as hydrogen bond acceptor) and Pro1074 (acting as hydrogen bond donor) found on the WPF and LPF loops respectively play in maintaining Cpd38 stability. Furthermore, the hydrogen bond acceptor/donator ratio was approximately 4:1 in Cpd38 -BRD4 system compared with 2:1 in Cpd38 -EP300 system. Taken together, atomistic insights and structural perspectives detailed in this report supplements the experimental report supporting the improved selectivity of Cpd38 for BRD4 ahead of other BCPs while providing leeway for the future design of BET selective agents with better pharmacological profile. Graphical Abstract: ga1 Highlights: Shape complementarity upon ligand binding plays a significant role in protein-ligand binding affinity. The ZA loop appears to be the most important region for ligand selectivity on BET proteins like BRD4. Selectivity of a ligand for BET proteins may prefer reduced structural flexibility at the WPF shelf of the protein.